Comparative analysis of SLA-1, SLA-2, and DQB1 genetic diversity in locally-adapted Kenyan pigs and their wild relatives, warthogs - Machuka, Eunice M.; Muigai, A.W.T.; Amimo, J.O.; Domelevo Entfellner, Jean-Baka; Lekolool, I.; Okoth, Edward A.; Pelle, Roger (MDPI, 2021)
Swine leukocyte antigen (SLA) plays a central role in controlling the immune response by discriminating self and foreign antigens and initiating an immune response. Studies on SLA polymorphism have demonstrated associations between SLA allelic variants, immune response, and disease resistance. The SLA polymorphism is due to host-pathogen co-evolution resulting in improved adaptation to diverse environments making SLA a crucial genomic region for comparative diversity studies. Although locally-adapted African pigs have small body sizes, they possess increased resilience under harsh environmental conditions and robust immune systems with reported tolerance to some diseases, including African swine fever. However, data on the SLA diversity in these pigs are not available. We characterized the SLA of unrelated locally-adapted domestic pigs from Homa Bay, Kenya, alongside exotic pigs and warthogs. We undertook SLA comparative diversity of the functionally expressed SLA class I (SLA-1, SLA-2) and II (DQB1) repertoires in these three suids using the reverse transcription polymerase chain reaction (RT-PCR) sequence-based typing (SBT) method. Our data revealed higher genetic diversity in the locally-adapted pigs and warthogs compared to the exotic pigs. The nucleotide substitution rates were higher in the peptide-binding regions of the SLA-1, SLA-2, and DQB1 loci, indicative of adaptive evolution. We obtained high allele frequencies in the three SLA loci, including some breed-specific private alleles, which could guide breeders to increase their frequency through selection if confirmed to be associated with enhanced resilience. Our study contributes to the growing body of knowledge on genetic diversity in free-ranging animal populations in their natural environment, availing the first DQB1 gene data from locally-adapted Kenyan pigs.